EXTH-32. TARGETED STAT3 INHIBITION IMPAIRS MDSC MOBILIZATION AND RECRUITMENT IN GLIOBLASTOMA - von Roemeling, Christina (Neuro Oncol, 2020)
BACKGROUND: Glioblastoma tumors (GBM) are comprised upwards of 30 percent by glioma-associated myeloid cells (GAMs). A large fraction of GAMs are myeloid-derived suppressor cells (MDSC) thought to traffic in from peripheral circulation. MDSCs foster a hospitable environment for cancer cells by regulating immune suppression and driving resistance to immunotherapy. While signal transducer and activator of transcription 3 (STAT3) is considered to be a specific marker for MDSCs and is a known player in their phenotypic polarization in cancer, we sought to closely examine its specific role in MDSC trafficking and tumor recruitment. HYPOTHESIS: Targeted inhibition of STAT3 blocks MDSC from the bone marrow, mitigating their accumulation within GBM tumors. METHODS: Human and murine GBM samples were analyzed for immune-specific STAT3 phosphorylation (P-STAT3). Immune cell characterization and quantification in peripheral and GBM tissue from syngeneic murine models treated with a novel STAT3 inhibitor (LLL12B) was done. Therapeutic responses to LLL12B alone and in combination with immune checkpoint blockade were evaluated. RESULTS: We found P-STAT3 to be predominantly expressed by tumor-associated immune cells in both human and murine GBM, particularly MDSCs. Circulating numbers of MDSCs dramatically increase in response to tumor burden. P-STAT3 is elevated in these cells, indicating that its activation occurs prior to tumor infiltration. LLL12B blockade of STAT3 significantly reduced the number of circulating and tumor-infiltrating MDSCs. As a single agent LLL12B reduced tumor volume and extended the survival of murine GBM models. When combined with anti-PD-1 checkpoint blockade, we observed durable survival in a significant fraction of treated mice. CONCLUSIONS: These findings advocate a critically important role for STAT3 in regulating MDSC mobilization and trafficking to GBM tumors. It additionally reveals a new therapeutic mechanism of action for LLL12B that may be relevant for other direct inhibitors of STAT3, influencing their clinical applicability to treat GBM.